Assessment of the Role of Luteal Phase Antagonist in Women at High-risk of Developing Ovarian Hyper-Stimulation Syndrome (OHSS) Receiving GnRH Agonist Trigger - Bakry, Ahmed; Mohammed, Passant Mohammed; Mohamed, Amal Shohayeb Ahmed; Kamal, Manal Mohamed; Fahmy, Radwa Mohamed; Abdelsalam, M.A.; Tamam, Amr Samir Fouad; Al-husseiny, Maha (Journal of Neonatal Surgery, 2025)
Background: Ovarian hyperstimulation (OHSS) is a serious complication of assisted reproductive technology (ART). This paper aims to assess the effectiveness of luteal phase cetrotide, administered for 3 days starting on the day of oocyte retrieval, on the incidence of mild and moderate ovarian hyperstimulation syndrome (OHSS) and vascular endothelial growth factor (VEGF) levels in females at high risk for the development of OHSS who receive the GnRH antagonist induction protocol. Patients and methods: The study included 110 infertile women candidates for IVF at high risk for OHSS, randomized into two cohorts: the cetrotide cohort (n=55) and the control (no-cetrotide) cohort (n=55). All participants received the conventional antagonist protocol, followed by the freeze policy. The control cohort received traditional symptomatic treatment. In addition to symptomatic treatment, the study cohort received a subcutaneous injection of cetrorelix acetate; all patients underwent clinical evaluation on days 0, 3, and 5. Then, on day 5 after oocyte retrieval, all patients underwent ultrasound scanning for ascites grading and maximum ovarian diameter (MOD). We took blood samples to determine the level of VEGF. Results: The results indicated that patients in both groups exhibited non-significant differences in terms of age, BMI, ovarian serum E2 on the day of trigger, and number of oocytes retrieved (P > 0.05). Day 3 VAS pain scores were significantly lower in both groups than the Day 0 scores (P = 0.000). On day 5, we found a statistically significant difference in MOD (P=0.000). Additionally, serum vascular endothelial growth factor levels on day -5 showed a statistically significant difference between the two groups (P = 0.000). The incidence of mild and moderate OHSS syndrome was significantly lower in the cetrotide cohort than in the control cohort (9.1% and 32.7%, respectively; P = 0.005). Conclusion: Administering the GnRH antagonist (cetrotide) during the luteal phase decreased the severity and frequency of early ovarian hyperstimulation syndrome symptoms in high-risk females with all embryos cryopreserved. Cetrotide may work by directly affecting the ovary, which could lead to lower levels of a substance called serum vascular endothelial growth factor.